Introductory letter from the Guest Editors - Poderoso, Juan José (2016)
As Guest Editors of Journal Pharmacology Research it is our pleasure to introduce the Special Issue Country in focus: Pharmacology in Argentina. Argentina has three Nobel Prize winners related to Medicine or Biology; it may not be a coincidence that each one of them was related to the world of Pharmacology. It also has given birth to a lot of scientists of high academic quality. Here are their biographical sketches.